3
$\begingroup$

$$\int_{-\infty}^{\infty} g(t)dt = \int_{0}^{\infty} \frac{\lambda^{\alpha}}{\Gamma(\alpha)} t^{\alpha - 1} e^{-\lambda t} dt = \frac{\lambda}{\Gamma(\alpha)} \int_{0}^{\infty} (\lambda t)^{\alpha - 1} e^{-\lambda t} dt$$

Set $u = \lambda t$:

$$= \frac{\lambda}{\Gamma(\alpha)} \int_{0}^{\infty} u^{\alpha - 1} e^{-u} du = \frac{\lambda}{\Gamma(\alpha)} {\Gamma(\alpha)} = \lambda$$

I've tried this proof several times and always end up with an extra $\lambda$. Each step seems pretty straightforward so I can't find what I'm overlooking.

$\endgroup$
5
$\begingroup$

In your substitution for $u = λt$ you did not correctly replace the $dt$ term: you only substituted $du$ for it. In fact, $du = λ dt$, which "consumes" the last remaining $λ$ left of the integral.

$\endgroup$
1
  • $\begingroup$ Can't believe I missed that... Thanks! $\endgroup$ – Y. Sargis Nov 22 '16 at 18:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.